Integrating Ethnopedagogy into Learning Media to Foster Positive Discipline among Elementary School Students: A Systematic Literature Review - Umah, Faikhotul; Subrata, Heru; Hitta, Hitta Alfi Muhimmah (Universitas Pendidikan Mandalika, 2026)
This study aims to explore the integration of ethnopedagogy in the development of learning media to strengthen positive discipline among elementary school students. The study employed a systematic literature review following PRISMA guidelines. A total of 18 empirical articles published between 2023 and 2025 were retrieved from the Scopus, Google Scholar, and DOAJ databases. The data were synthesized using thematic analysis, focusing on ethnopedagogy-based learning media, the effectiveness of pop-up books, and positive discipline practices in inclusive classrooms. The results indicate that ethnopedagogy-based learning media—including interactive videos, digital modules, traditional arts, and augmented reality applications—effectively enhance character values such as cooperation, environmental awareness, integrity, and discipline. Pop-up books demonstrate considerable potential in fostering positive behavior, self-confidence, and learning motivation, although limited studies specifically address discipline and prosocial behavior. Furthermore, positive discipline practices that incorporate local cultural values, indigenous learning approaches, and restorative practices show promising outcomes in creating inclusive classroom environments and reducing exclusionary discipline. The integration of local cultural wisdom through ethnopedagogical approaches provides culturally relevant contexts that enhance student engagement and the internalization of positive discipline values. This review contributes novel insights by proposing a multimodal integration framework that combines indigenous values with diverse learning media formats, addressing a gap in the literature where ethnopedagogy and positive discipline have rarely been examined together. However, challenges remain regarding scalability, teacher training, and the need for longitudinal impact evaluation.